Legal Responsilibility of affiliators who spread misleading product promotions that harm consumers - Muhammad Adli Fahmi Lubis; Sunarmi; Mahmul Siregar; Robert (Journal Equity of Law and Governance, 2024)
Binomo as one of the trading platforms has taken a lot of casualties, due to the presence of affiliates who facilitate huge profits in a short period of time. Influencer and affiliate Indra Kents were named as a suspect. It should be noted that misleading advertising formats that cause consumer losses, the mechanism by which affiliated companies can compensate consumers, and the legal liability of affiliated companies that advertise items that result in losses for customers. Using a philosophical and legislative approach, this research is normative in nature. Utilizing primary, secondary, and tertiary legal documents gathered through literature study methodologies, the data comes from secondary data sources. A qualitative data analysis method is employed. The investigation came to the conclusion that deceptive advertising that presents success stories and offers affiliates the promise of enormous earnings are among the deceptive tactics that harm consumers. A demand for compensation can be made both civilly and UUPK in order to reimburse victims of Binary Option criminality for their damages. In combination with ITE Law's Article 28 paragraph (1) and Article 45A paragraph (1), Article 1365 of the Civil Code both contain legal liability provisions for affiliates that push products that result in losses for consumers. Article 62 paragraph (1) of the Law may impose sanctions on the affiliator, in reference to letter k of Article 9 paragraph (1) of the UUPK.